Microstructure Evolution in Dissimilar AA6060/Copper Friction Stir Welded Joints; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Kalashnikova T. V. Tatiana Vladimirovna (2017, 2017)
Title screen